परिमाणात्मक विधियाँ - Bhardwaj, J.L.; Ganesh Kavadia (Madhya Pradesh Hindi Granth Academy, 2016)
The book describes the various quantitative techniques in economic development and research.
Quantitative Techniques
Keywords: परिमाणात्मक विधियाँ; Quantitative Techniques; Economics; Hindi; Hindi